Structural organization of long-range GABAergic projection system of the hippocampus - Jinno, Shozo (Frontiers in Neuroanatomy, 2009)
GABA is a key mediator of neural activity in the mammalian central nervous system, and a diverse set of GABAergic neurons utilize GABA as transmitter. It has been widely accepted that GABAergic neurons typically serve as interneurons while glutamatergic principal cells send excitatory signals to remote areas. In general, glutamatergic projection neurons monosynaptically innervate both principal cells and local GABAergic interneurons in each target area, and these GABAergic cells play a vital role in modulation of the activity of principal cells. The formation and recall of sensory, motor and cognitive representations require coordinated fast communication among multiple areas of the cerebral cortex, which are thought to be mostly mediated by glutamatergic neurons. However, there is an increasing body of evidence showing that specific subpopulations of cortical GABAergic neurons send long-range axonal projections to subcortical and other cortical areas. In particular, a variety of GABAergic neurons in the hippocampus project to neighboring and remote areas. Using anatomical, molecular and electrophysiological approaches, several types of GABAergic projection neurons have been shown to exist in the hippocampus. The target areas of these cells are the subiculum and other retrohippocampal areas, the medial septum and the contralateral dentate gyrus. The long-range GABAergic projection system of the hippocampus may serve to coordinate precisely the multiple activity patterns of widespread cortical cell assemblies in different brain states and among multiple functionally related areas.